Answer:
3) f'(x) = x + 10
4) f'(x) = 6x - 18
5)
or
6) f'(x) = ⅛x or
Explanation:
3. f(x) = x - 10
Step 1: In order to find the inverse function of f(x) = x - 10, start by replacing f(x) with y.
y = x - 10
Step 2: Switch x and y:
x = y - 10
Step 3: Add 10 to both sides to isolate y:
x + 10 = y - 10 + 10
x + 10 = y
Step 4: Replace y with f'(x):
f'(x) = x + 10 ⇒ This is the inverse function of f(x).
4.
![\displaystyle\mathsf{f(x)=\:(x)/(6)\:+\:3}](https://img.qammunity.org/2022/formulas/mathematics/college/wm3kkz03vd47sfh0zqwl3k7jxxrqzh2f6w.png)
Replace f(x) with y:
![\displaystyle\mathsf{y=\:(x)/(6)\:+\:3}](https://img.qammunity.org/2022/formulas/mathematics/college/aalwh0mtllroar33jwpyy0mwzjypvdfmc3.png)
Switch x and y:
![\displaystyle\mathsf{x=\:(y)/(6)\:+\:3}](https://img.qammunity.org/2022/formulas/mathematics/college/lyg020hotnqkpy3lts7n7nveui5rurwlxe.png)
Subtract 3 from both sides:
![\displaystyle\mathsf{x-3=\:(y)/(6)\:+\:3-3}](https://img.qammunity.org/2022/formulas/mathematics/college/wb3va7dm2czk307b2pc0mo016q352u02vn.png)
![\displaystyle\mathsf{x-3=\:(y)/(6)}](https://img.qammunity.org/2022/formulas/mathematics/college/r5fjlz79nxnpwfsfz7dghf11fid2mahi8y.png)
Multiply both sides by 6 to isolate y:
![\displaystyle\mathsf{6(x-3)=\:(y)/(6)(6)}](https://img.qammunity.org/2022/formulas/mathematics/college/8zkbty3ze3eo1rx98ls6frriwocb56kl3i.png)
6x - 18 = y
Replace y with f'(x):
f'(x) = 6x - 18 ⇒ This is the inverse function of f(x).
5. f(x) = 3x + 7
Replace f(x) with y:
y = 3x + 7
Switch x and y:
x = 3y + 7
Subtract 7 from both sides:
x - 7 = 3y + 7 - 7
x - 7 = 3y
Multiply both sides by ⅓:
⅓(x - 7) = 3y (⅓)
![\displaystyle\mathsf{(1)/(3)x-(7)/(3)=y}](https://img.qammunity.org/2022/formulas/mathematics/college/4bcp3l9pg7ds8o9q7oyogn4j6tdu6r7wyt.png)
Replace y with f'(x):
or
⇒ This is the inverse function of f(x).
6. f(x) = 8x
Replace f(x) with y:
y = 8x
Switch x and y:
x = 8y
Multiply both sides by ⅛:
⅛(x) = ⅛(8y)
⅛x = y or
Replace y with f'(x):
f'(x) = ⅛x or
⇒ This is the inverse function of f(x).